Identifikasi Faktor yang Memengaruhi Intensitas Pengggunaan Trans Metro Pasundan - Azmi Muhammad Fadhlurrohman Rata Agustina (IAI Nasional Laa Roiba Bogor, 2024)
Bandung is experiencing increasing traffic congestion due to the city's expansion and rapid population increase. Congestion is a direct result of increasing traffic volume, which is closely related to adequate infrastructure development. Based on the Bandung City BPS report in 2021, the number of motorized vehicles reached 1.5 million. Given the continued prevalence of private car use, it is important to ascertain the extent to which people use public transport. Intensity of use of public transport. Trans Metro Pasundan is a Bus Rapid Transit (BRT) scheme known as Buy The Service (BTS) which was initiated by the Ministry of Transportation of the Republic of Indonesia. This research aims to identify factors that influence the intensity of use of Trans Metro Pasundan public transportation. Analysis of the movement characteristics of TMP users was carried out using the cross tabulation analysis method to determine the factors that influence passengers in using Trans Metro Pasundan in Bandung City. So from the analysis that has been carried out, the intensity of use of Trans Metro Pasundan is due to the route factors available on the Trans Metro Pasundan corridor.